Using Population Survey Data to Model Determinants of HIV Status and Sexual Risk Behaviours - Patocs, Audrey E. (My University, 2013)
Sub-Saharan Africa (SSA) continues to be disproportionately burdened by the HIV/AIDS epidemic. In 2011, the region saw 1.8 million new infections, contributing to a prevalence of 4.9% among adults, or 23.5 million people living with HIV/AIDS. This thesis uses data collected by the Demographic and Health Surveys (DHS) to answer questions about risk factors and behaviours associated with HIV acquisition. I use logistic regression models to assess the impact of purported risk factors on sexual behaviours and HIV status. In Chapter One, I evaluate the association between respondents' condom use and their awareness of their own \local" epidemic. In Chapter Two, the association between hormonal contraceptives and risk of HIV infection is examined. The purpose of these analyses is to contribute to the body of literature that identifes factors that mitigate or contribute to risk for HIV infection, and help to inform public health policy.
Keywords: HIV; Epidemiology; Condom; Contraceptive; Modelling; Risk; Health Policy; Health Policy